Narrativising women empowerment in India - Chakrabarty, Bidyut (2015)
Gender equality and women empowerment are two critical pillars of inclusive development. Despite being half of the population, women never seem to have obtained what they deserve from society presumably because of well-entrenched patriarchal bias. Needless to say, there are innumerable progressive legislations addressing this socio-economic imbalance; nonetheless, they continue to remain at the receiving end given the prevalence of the mindset upholding well-entrenched prejudices. How to combat such a mindset? Drawn on empirical data, the article argues that education is a great leveler. By focusing on various schemes relating to women empowerment, the article further shows that the well-entrenched prejudiced mindset can be effectively combated by making women aware of their rights and also by raising their voice in case they are infringed. It is easier said than done. Nonetheless, specific legal stipulations to challenge patriarchal prejudices in the socio-economic system need also to be complemented by parallel movements involving the masses regardless of gender; otherwise, the entire exercise, the article underlines, shall become futile. In that sense, movements for women empowerment and gender equality do not seem to be exclusive, but inclusive both in aims and agenda-setting. - Reproduced.
Keywords: Women - India; Women